Pengaruh Metode Latihan dan Motivasi Berprestasi Terhadap Kemampuan Lay Up Shoot Permainan Bola Basket Ekstakulikuler Siswa SMP N 1 Watampone - Harliawan, Muhammad; Dos Santos, Maria Herlinda; Okilanda, Ardo (Jurnal MensSana, 2021)
The purpose of this study is to determine the effect of the methods section training and methods overall training motivation achievement shoot lay-up skills in the game of basketball The research is conducted at extracurricular student SMP 4 Watampone ,This study is using treatment by level 2 x 2. The samples are consisted of 40 student. The technique of data analysis is two ways analysis of variance (ANAVA) and followed by Tuckey's test for significance level of α = 0, 05. The results of this study show that (1) score for method training section (A1) is higher than the method of overall training (A2) at extracurricular student SMPN 1 Watampone ; (2) there is an interaction between practice methods (A) and training motivation (B) shoot lay-up skills in the game of basketball; (3) score of high method section training (A1B1) is higher than score of high method overall training (A2B1); 4) score of low method section training (A1B2) is lower than score of low method overall training (A2B1)